Relation between preparation art and chemical properties of modified Kieselguhrs – a nanoscale surface analysis. (4th December 2009) - Smejkal, Q.; Pohl, M-M.; Bentrup, U.; Martin, A.; Schleicher, T.; Russ, W.
Kieselguhr is mostly applied as a filter material. For practical utilisation, its particle size should be enlarged. Such agglomeration occurs during calcination, supported by fluxing agents. Unfortunately, calcination at elevated temperatures initiates a formation of cristobalite, which is classified as a carcinogenic component. The main objective of this paper is thus to reveal differences between preparation processes and surface structure changes resulting from calcination. Achieved results elucidate the correlation between art of calcination and surface properties of the product. Calcination experiments in presence of Na2CO3 showed much higher cristobalite formation compared to calcination of pure Kieselguhr. The wet impregnation method results in desired particle enlargement, but leads also to total destruction of the internal structure of the particles. In spite of desired particle enlargement, the dry processing enables to keep fine filtration characteristics of the final Kieselguhr material and moreover is much easier for high-capacity industrial production.